Moving to condominium housing? Views about the prospect among children and their families in Addis Ababa and Hawassa - Tiumelissan, A; Pankhurst, A (Young Lives, 2013)
This paper considers the views of caregivers and children in four sites in Addis Ababa and Hawassa about a condominium housing programme established by the government of Ethiopia with the intention of providing low-cost housing for the urban poor, especially for those living in sites designated for redevelopment. The paper provides insights into the ways in which the Young Lives children and adults perceive this new form of housing, what they appreciate and what they dislike about it, the extent to which they would wish to live there, and their assessment of whether they will be able to afford the costs. The paper also presents the views of officials and community leaders, as well as case studies of a few households which have already moved into condominium housing. The perspectives of families who will be directly affected by urban redevelopment have important policy implications in terms of addressing the needs of the urban poor, their preferences and priorities. The findings suggest the need for a range of options for financing access to condominiums for the urban poor, including more flexible, longer-term, inter-generational or group loans, and the formation of housing cooperatives. Alternatives to the condominium model should also be considered, since it does not seem to be a realistic option for the very poor without the benefit of subsidies.